On the distribution and habitat of Fuscopannaria leucosticta in New Brunswick, Canada. Issue 2 (3rd April 2019) - Haughian, Sean R.; Clayden, Stephen R.; Cameron, Robert
ABSTRACT: Fuscopannaria leucosticta is a rare lichen that exhibits an apparent specificity for old wet forests in eastern Canada, and may, consequently, be sensitive to anthropogenic disturbance. Estimates of the current distribution and population size are highly uncertain. Effective conservation planning requires improving our understanding of both its current distribution and the factors that influence habitat suitability. We built a MaxEnt distribution model with interpolated climate data, depth to water table mapping, forest inventory data, and herbarium collection data for F. leucosticta in New Brunswick, Canada. We tested model performance via field verifications in high-probability areas with no record of previous surveys. We found F. leucosticta in 13 out of 22 previously unsurveyed locations with a predicted high probability of occurrence. Selected variables included the presence of cedar in the canopy and a lack of recent anthropogenic disturbance, as well as mean annual rainfall and degree days above 0°C. These associations are likely a result of the lichen's low reproductive output and the thermal and hydration requirements of its cyanobacterial photobiont. Our study affirms several previous claims about habitat associations of the species, and provides focus for conservation efforts in the future.